Financial leverage effect towards the profitability of the Malaysian Public financial institutions / Umi Hazimah Zohari - Zohari, Umi Hazimah (2017)
This research is conduct in order to see the effect of financial leverage towards the profitability of the public financial institutions in Malaysia. The ratio that has been used in this study is Profitability, return on assets (ROA) as the dependent variable and Financial Leverage, debt ratio (DRTO), debt to equity ratio (DERTO) and debt to ebitda (DEBDA) as the independent variables. The result shows that DRTO has a positive correlation with ROA while DERTO and DEBDA have a negative relationship ROA.